A computational approach for modeling the indexical field / Uma abordagem computacional para a modelagem de campos indexicais (Revista de Estudos da Linguagem, 2019)
Abstract: This study investigates how multiple social meanings come to be associated with a linguistic variable. The analyses of listeners’ perceptions of tap and retroflex realizations of coda /r/ in São Paulo Portuguese (as in jornal ‘newspaper’ and bazar ‘bazar’), through an experiment based on the matched-guise technique (LAMBERT et al., 1960; CAMPBELL-KIBLER, 2006, 2009) applied to 185 participants, show that coda /r/ in São Paulo is strongly associated to geographical identities, from which further inferences arise on speakers’ social status regarding their social class, area of residence, level of education, along with personal traits such as being “articulate” and “hardworking.” Interactions between variable /r/ and participants’ social profiles are explored, as well as the fact that certain plausible correlations do not arise, particularly in comparison to previous perception studies. In problematizing the nature of the ideological inter-relations among multiple factual and potential social meanings, an objective and falsifiable computational method for modeling indexical fields is proposed, based on Minimum Spanning Trees (GOWER; ROSS, 1969).Keywords: indexical fields; social meanings of variation; coda /r/; São Paulo Portuguese; matched-guise technique; computational models of language variation.Resumo: Este trabalho investiga de que modo múltiplos significados sociais vêm a se associar a uma variável sociolinguística. As análises de percepções de ouvintes sobre as realizações de /r/ em coda como tepe ou retroflexo no português paulistano (como em jornal e bazar), por meio de um experimento com base na técnica de estímulos pareados (LAMBERT et al., 1960; CAMPBELL-KIBLER, 2006, 2009) aplicado a 185 participantes, mostram que a variável /r/ se associa fortemente a identidades geográficas, a partir das quais surgem inferências sobre o status social dos falantes com relação a sua classe social, região de residência, nível educacional, juntamente a traços pessoais como ser uma pessoa “articulada” ou “trabalhadora”. Exploram-se as interações entre a variável /r/ e os perfis sociais dos participantes, assim como o fato de que certas correlações não se manifestam, particularmente em comparação com outros estudos prévios. Ao problematizar a natureza das inter-relações ideológicas entre múltiplos significados factuais e potenciais, propõe-se um método computacional objetivo e falseável para a modelagem de campos indexicais, com base em Árvores de Distâncias Mínimas (GOWER; ROSS, 1969).Palavras-chave: campos indexicais; significados sociais da variação; /r/ em coda; português paulistano; técnica de estímulos pareados; modelos computacionais da variação linguística.